Pitiose nasal em equino - D'Utra Vaz, B. B.; Maia, F. C L; Rocha, Noeme Sousa [UNESP]; Thomassian, A. [UNESP] (My University, 2009)
Pythiosis is a subcutaneous infection caused by aquatic fungi (Pythium insidiosum) which occurs in some animal species, as human beings. This paper describes an Quarter Horse, breed in Pernambuco, Brazil, who had this infection. The horse presented nodular and ulcerated lesions only in nasal mucosa and the diagnosis was made by histopathologic analysis and clinical signals. Based in the histopathologic findings and anamneses information by the owner the authors believed this is an atypical presentation of this infection caused by the contact with water offered at stable.
Nasal pythiosis in horse
Keywords: Fungus; Kunker; Pythium insidiosum; Animalia; Equidae; Fungi; Pythium